Study of BaTiO3-doped Bi2O3/ZnO varistor microstructure and its electrical characteristics - Kharchouche, Faiçal; Malaoui, Yousra; Bouketir, Omrane (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This study presents the characterization and optimization of BaTiO3-doped ZnO-based varistors for electrical and electronic applications. The varistors were prepared using a conventional ceramic procedure and were sintered at a temperature of 1,000 °C with different concentrations of BaTiO3 (0 and 3 mol%) added to the Bi2O3/ZnO-based varistor composition (99.5 mol% ZnO and 0.5 mol% Bi2O3). The results showed that the addition of BaTiO3 led to the formation of various oxides and solid solutions, such as Bi12TiO20, BaTiO3, and (Bi2O3)0.80 (BaO)0.20. The dielectric constant and grain size decreased with increasing BaTiO3 content, while the non-linearity coefficient, electric fields (Eb) increased, and dielectric loss (Tanδ) decreased. The optimized varistor contains 2 mol% BaTiO3 and an electric field of 148.08 V/mm, which are superior to those of the BaTiO3/Bi2O3/ZnO-based varistor. During this study, we were able to observe that a slight addition of BaTiO3 will increase the breakdown voltage and the coefficient of nonlinearity and this will allow us to develop low-dimensional varistors and install them in the high-voltage domain.